Transformational leadership enhances customer satisfaction - Nor Mohd Desa, Kamariah; Ahmad Kassim, Norliya (Persatuan Pustakawan Malaysia, 2010)
This paper discusses about transformational leadership that enhances customer satisfaction. It covers briefly related issues such as leadership, transformational leadership, total quality management (TQM), quality management system (QMS) ISO 9001:2008, and customer satisfaction. The discussion is focus on how these issues are interrelated to each other specifically on their applicability to increase high performance for library services, and the impact of effective leadership that contributes significantly to the outcome of performance beyond expectations. The Universiti Teknologi Malaysia Library showcases findings on the customer satisfaction surveys from 2006 to 2009.